Nuclear power plants: safe during war? - Chew, Alvin (2022)
Nuclear deterrence strategy has so far prevented the world superpowers from engaging in a nuclear armed conflict. But could a nuclear dystopia be averted when a civilian nuclear power plant is accidentally attacked during a war?